ANALISIS KINERJA USAHA PEMBUATAN IKAN KERING DI KOTA BENGKULU - Sumantri, Bambang; Purwoko, Agus; Sriyoto, Sriyoto (Jurnal AGRISEP, 2016)
The aim of this study was to assess the performance of the business of dried fish processor were approached by the amount of income and the value of the economic efficiency of the business. The study was conducted in the city of Bengkulu in March to June 2015 by surveying 55dried fish processorpurposively. Data were analyzed descriptively that utilizes primary data and analyzed by income value approach and economic efficiency. The results showed total revenue the business of making dried fish Rp 2,312,925.00 or receiving one year is Rp.92.517.019, 00. Total variable costs are devoted to produce dried fish amounted to 99.50%, while total fixed costs amounted to only 0.5%. 99,50 % from the variable cost are 46.17% used for the purchase of raw materials and 35% to buy ice cubes, while the fixed costs only Rp. 9819.95, or 0.50% of the total costs. Overall the total cost of the production process of making the effort to dry in the study area is Rp. 2,000,178.35 every week . If taken into account in cash the business of making dried fish in a week will earn a revenue of Rp 312,747.12 or if calculated with non-cash expenses, the revenues of Rp.626.055,25 every week. If the business activities run continuously, then in a month of dried fish making business will generate income of Rp.2.504.221,00. Efficient economic level (R / C) at 1.15. This measurement shows that this business has a relatively good performance for relatively efficient.